PEMODELAN SIKLUS IN-CYLINDER MESIN DIESEL - Bagus Anang Nugroho; Rizqon Fajar; Ihwan Haryono (BRIN, 2018)
An engine performance can be predicted through modeling and simulation programs. This paper describes the cycle modeling and breathing process of a four-stroke diesel engine. Calibration of the model parameters to eliminate prediction error. This calibration requires the definition of empirical correlation of two parameters namely mechanical delay and the injector nozzle discharge coefficient. Modeling validation is also given by presenting the result data and evaluating the output parameters of the engine. The result of the diesel engine in-cylinder model produces good predictions by applying a mechanical delay correlation for correction of injection time and correlation coefficient of discharge nozze injector. The parameters for correction of injection duration where the mean temperature and pressure conditions for the duration of the injection are used as input model ignition delay cylinder.Keywords: Modeling, Diesel Engine, Performance, Ignition Delay, EmissionsÂ